Hospital payment schemes and high-priced drugs: Evidence from the French Add-on List. Issue 7 (July 2021) - Rachet-Jacquet, Laurie; Toulemon, Léa; Rochaix, Lise
Highlights: Drug delisting constitutes a major incentive change for hospitals. Delisting often occurs after patent loss and sharp price decreases. Drug prices do not decrease further after delisting. Prescription volumes are not affected by price regulations. Delisting is not associated with changes in the share of generic drugs. Abstract: Under prospective payment schemes, hospitals may be disincentivised to use high-priced drugs. In this context, supplementary payment schemes have been implemented to fund hospitals beyond hospital tariffs for the use of such technologies. In France, since 2004, an add-on list scheme ensures that listed high-priced drugs are reimbursed by the state, thereby imposing no cost on hospitals while drugs are on the list. Yet little is known about the impact of drug delisting, i.e., when drugs are removed from the add-on list, on hospital utilisation. In this paper, we investigate the effects of delisting for 12 cancer drugs on the volumes prescribed, the generic shares and the purchase prices negotiated by hospitals. Using French hospital-level data over the period 2008-2016, we construct volumes, generic shares and purchase prices at the molecule level to account for potential substitutions across therapeutically equivalent drugs. Hospital fixed effects allow for time-invariant unobserved hospital heterogeneity linked to e.g., prescription preferences or hospitals' bargaining power. Our results indicate that prescription volumes, generic shares and price levels are not systematically affected by delisting, nor do we find evidence of response heterogeneity by hospital type. Overall, our findings mitigate concerns that the financial incentives associated with add-on lists may lead to hospitals over-prescribing high-priced drugs.